The effect of human saliva compared to Aloe vera on wound healing of 2nd degree burn injury in animal models - Budi Cahyono Putro; Ishandono Dachlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Burn injury is one of the common causes of injury that has relatively high morbidity and mortality. Several studies using herbal and traditional medicine from different countries have been documented in burn injury management. Human saliva that contains antibacterial, antifungal, antiviral and analgesic components as well as growth factors can induce re-epithelialization process in 2nd degree burn injury. Whereas, Aloe vera that influence a physiological moist condition was proven can induce re-epithelialization process lead to faster wound healing. This study aimed to compare topical application of human saliva and A. vera on wound healing process of 2nd degree burn injury. This was an experimental study using post-test only control group design using 27 white rats (Rattus novergicus) of Sprague Dawley strain divided into 3 groups with 9 rats in each group. Group I were applied 1 mL of human saliva, Group II were applied A. vera and Group III as control were applied NaCl. Change in body weight and macroscopic clinical assessment were observed every day for 14 days, whereas histological examination was observed on day 14. The data were presented as mean ± standard error of the mean (SEM) and analyzed using one-way analysis of variance (Anova). The result showed that the wound healing process at each treatment showed different level. The human saliva application tended to show faster wound healing process of 2nd degree burn injury compare with A. vera or NaCl (p